Deciphering the functional heterogeneity of skin fibroblasts using single‐cell RNA sequencing. Issue 3 (12th January 2020) - Vorstandlechner, Vera; Laggner, Maria; Kalinina, Polina; Haslik, Werner; Radtke, Christine; Shaw, Lisa; Lichtenberger, Beate Maria; Tschachler, Erwin; Ankersmit, Hendrik Jan; Mildner, Michael
Abstract: Though skin fibroblasts (FB) are the main cell population within the dermis, the different skin FB subsets are not well characterized and the traditional classification into reticular and papillary FBs has little functional relevance. To fill the gap of knowledge on FB diversity in human skin, we performed single‐cell RNA sequencing. Investigation of marker genes for the different skin cell subtypes revealed a heterogeneous picture of FBs. When mapping reticular and papillary FB markers, we could not detect cluster specificity, suggesting that these two populations show a higher transcriptional heterogeneity than expected. This finding was further confirmed by in situ hybridization, showing that DPP4 was expressed in both dermal layers. Our analysis identified six FB clusters with distinct transcriptional signatures. Importantly, we could demonstrate that in human skin DPP4 + FBs are the main producers of factors involved in extracellular matrix (ECM) assembly. In conclusion, we provide evidence that hitherto considered FB markers are not ideal to characterize skin FB subpopulations in single‐cell sequencing analyses. The identification of DPP4 + FBs as the main ECM‐producing cells in human skin will foster the development of anti‐fibrotic treatments for the skin and other organs.